RhoH regulates subcellular localization of ZAP-70 and Lck in T cell receptor signaling. - Hee-Don Chae; Jamie E Siefring; David A Hildeman; Yi Gu; David A Williams (PLoS ONE, 2010)
RhoH is an hematopoietic-specific, GTPase-deficient Rho GTPase that plays a role in T development. We investigated the mechanisms of RhoH function in TCR signaling. We found that the association between Lck and CD3ζ was impaired in RhoH-deficient T cells, due to defective translocation of both Lck and ZAP-70 to the immunological synapse. RhoH with Lck and ZAP-70 localizes in the detergent-soluble membrane fraction where the complex is associated with CD3ζ phosphorylation. To determine if impaired translocation of ZAP-70 was a major determinant of defective T cell development, Rhoh(-/-) bone marrow cells were transduced with a chimeric myristoylation-tagged ZAP-70. Myr-ZAP-70 transduced cells partially reversed the in vivo defects of RhoH-associated thymic development and TCR signaling. Together, our results suggest that RhoH regulates TCR signaling via recruitment of ZAP-70 and Lck to CD3ζ in the immunological synapse. Thus, we define a new function for a RhoH GTPase as an adaptor molecule in TCR signaling pathway.